Regenerative therapy of bony peri-implant defects - a case report. Regenerative Therapie periimplantärer knöcherner Defekte - ein Fallbericht - Lutz, Rainer; Neukam, Friedrich Wilhelm; Schlegel, Karl Andreas (Implantologie, 2009)
With an increasing number of implants being placed, the treatment of peri-implant infections is becoming a focus of implantologists. Successful treatment of peri-implantitis involves the combined treatment of the peri-implant inflammation, implant surface decontamination, bone regeneration of the peri-implant defects, and reosseointegration of previously contaminated implant surfaces. Thereby, the individual steps limit one another. Recent research suggests that peri-implant defects can be successfully treated by a careful cleaning of the implant surface in combination with surgical and regenerative therapy, and appropriate antibiotic treatment if necessary. A successful therapy, according to these standards, is presented in this case report.
CRIS-Team Scopus Importer:2024-05-13
Keywords: Antibiotic therapy; Bone regeneration; Bone substitute material; Implant surface decontamination; Peri-implantitis; Re-osseointegration